2011
DOI: 10.1103/physrevlett.106.027401
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Calculations of the Urbach Tail in the Optical Absorption Spectra of Silica Glass

Abstract: We present density-functional theory calculations of the optical absorption spectra of silica glass for temperatures up to 2400 K. The calculated spectra exhibit exponential tails near the fundamental absorption edge that follow the Urbach rule in good agreement with experiments. We discuss the accuracy of our results by comparing to hybrid exchange correlation functionals. We show that the Urbach rule holds in a frequency interval where optical absorption is Poisson distributed with very large statistical flu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 33 publications
1
31
0
Order By: Relevance
“…Based on this approach, it is shown how damage initiation may occur because of a strong nonlinear growth of energy coupling. In particular, the formation of an absorption front (AF), moving at a speed one order of magnitude slower than the sound speed, is predicted, consistent with experiments [24] and other models [21]. This mechanism is essentially expected at the beginning of the interaction where the material undergoes major change of its electronic, optical and structural properties.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Based on this approach, it is shown how damage initiation may occur because of a strong nonlinear growth of energy coupling. In particular, the formation of an absorption front (AF), moving at a speed one order of magnitude slower than the sound speed, is predicted, consistent with experiments [24] and other models [21]. This mechanism is essentially expected at the beginning of the interaction where the material undergoes major change of its electronic, optical and structural properties.…”
Section: Introductionsupporting
confidence: 80%
“…More recently, observation of induced absorption in glasses due to ultrashort laser pulse exposure has also been reported [20]. Additionally, recent density-functional theory calculations [21] have shown that silica absorption spectra are expected to exhibit exponential tails near the band edge at elevated tempertatures.…”
Section: Introductionmentioning
confidence: 89%
“…This band tailing is a combination of the Urbach tail region characteristic of the amorphous hosts and a weak absorption tail region due to the localized defect centers as can be clearly seen in the log plot of the base glass absorption coefficient in Fig. 2 [11,12]. This band tailing gives rise to a non-zero absorption in the band gap region [12].…”
Section: Optical Absorptionmentioning
confidence: 80%
“…On a single-particle level, the latter is related to the dielectric function and thus the absorption coefficient as discussed for example, in Ref. 59. One can therefore expect a correlation between characteristic features in the absorption spectrum with features in the JDOS.…”
mentioning
confidence: 99%